2016
DOI: 10.15740/has/ijpp/9.2/424-429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioagents and chemicals for the management of aerial blight and dry root rot of blackgram incited by Rhizoctonia bataticola

Abstract: Blackgram (Vigna mungo L.) is an important pulse crop grown throughout India. A new disease of blackgram i.e. aerial blight and dry root rot caused by Rhizoctonia bataticola is primarily a soil inhabitant. An attempt was made to manage the disease with biocontrol agents and fungicides. Among the biocontrol agents tested against Rhizoctonia bataticola, Pseudomonas fluorescens (DAPG +ve)-RP46 was found more effective as compared to other bio-control agents and inhibited maximum mycelia growth (68.95%) of R. bata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Among the seven Trichoderma spp, T. harzianum inhibited maximum of 77.77%. Similar results were published bySangappa and mallesh (2016). Thombre B.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Among the seven Trichoderma spp, T. harzianum inhibited maximum of 77.77%. Similar results were published bySangappa and mallesh (2016). Thombre B.…”
supporting
confidence: 92%
“…The results stated that tebuconazole 50%+ trifloxystrobin 25% W G fungicide reported maximum inhibition of mycelial growth at 100 ppm followed by carbendazim 12%+ mancozeb 63% WP. Sangappa and Mallesh (2016) revealed that cent per cent mycelial growth inhibition was seen in treatment with carbendazim at 0.05, 0.1 and 0.2%.concentrations. Kumar Screening of Different Bioagents and Fungicides against Dry Root Rot of Chickpea Incited by Macrophomina phaseolina (Tassi) Goid et al (2021) found that tebuconazole 25.9% EC was most effective in inhibiting the mycelial growth of the pathogen followed by trifloxystrobin 25% + tebuconazole 50% W G.…”
Section: Screening Of Different Bioagents and Fungicides Against Dry ...mentioning
confidence: 96%
“…The results are in accords with work of the Maruti et al, (2017) found that carbendazim 12% + mancozeb 63% WP, carboxin 37.5% + thiram 37.5% WP showedcent per cent of inhibition of R. bataticola at all the concentrations i.e., 0.10%, 0.20% and 0.30%. Sangappa and Mallesh (2016) observed that carbendazim 12% + mancozeb 63%, showed complete inhibition of mycelial growth at all the concentrations, i.e., 0.05, 0.10 and 0.2%.…”
Section: Effect Of Ready-mix Fungicides On Growth Inhibition Of M Phaseolinamentioning
confidence: 89%
“…Maruti et al, (2017) reported that mancozeb and thiram showed 100 per cent inhibition at 0.3 per cent concentration. Sangappa and Mallesh (2016) recorded that the fungicides thiophanate methyl and triadimefon showed 100 per cent mycelia inhibition at 0.1, 0.2 and 0.3%.…”
Section: Effects Of Non-systemic Fungicides On the Growth Of M Phaseolinamentioning
confidence: 99%
“…Bavistin (2 g kg-1 seed) + neem extract (20%) was the most effective treatment with 67.3% reduction followed by T. harzianum (15 g kg-1 seed) + Bavistin (54.2%). (Ramadoss andSivaprakasam (1994), Prajapati et al, (2002) and Sangappa and Mallesh (2016). Khan et al, (2012) reported that indofilm-45, Bavistin, companion, copperoxycloride and Benelate were completely inhibited the growth of the fungus on potato dextrose agar medium.…”
Section: B: C Ratiomentioning
confidence: 98%